The Impact of Environmental, Social, and Governance Disclosure on Firm Value: Evidence from Energy and Basic Materials Companies in Indonesia - Herni Ponia; Yusron Toto (Journal of Business Economics : Needs, Services, and Money, 2026)
This study aims to examine the influence of environmental, social, and governance disclosure on company value (PBV and Tobin's Q). While the independent variables are environmental and social, then governance. The population in this study is energy and basic materials sector companies listed on the Indonesia Stock Exchange for the 2017- 2023 period. The sampling method used is the purposive sampling method so that 7 companies were obtained. The total number of data processed in this study is 49 data. The type of data used is secondary in the form of annual financial statements of companies in the energy and basic materials sectors listed on the Indonesia Stock Exchange for the 2017- 2023 period. The data analysis method used in this study is descriptive statistics with a significant level value of 5%. The results of this study show that ESG has an effect on the company's value (PBV and Tobin's Q). Keywords: Environmental, Social, Governance, Corporate Value